2021
DOI: 10.3390/foods10123093
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Bacillus subtilis for Adhesion Inhibition of Pseudomonas and Preservation of Fresh Fish

Abstract: Inhibiting the growth of spoilage bacteria, such as Pseudomonas spp., is key to reducing spoilage in fish. The mucus adhesion test in vitro showed that the adhesion ability of Bacillus subtilis was positively correlated with its inhibition ability to Pseudomonas spp. In vivo experiments of tilapia showed that dietary supplementation with B. subtilis could reduce the adhesion and colonization of Pseudomonas spp. in fish intestines and flesh, as well as reduce total volatile basic nitrogen (TVB-N) production. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Mucus was prepared using the method published by Chen et al [14] with slight modification. The adhesion rate was determined according to Zhang et al [12].The adhesion rate was calculated using Equation (1).…”
Section: Determination Of Adhesion In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…Mucus was prepared using the method published by Chen et al [14] with slight modification. The adhesion rate was determined according to Zhang et al [12].The adhesion rate was calculated using Equation (1).…”
Section: Determination Of Adhesion In Vitromentioning
confidence: 99%
“…TVB-N was determined following the method described by Zhang et al [12], and calculated using Equation ( 2…”
Section: Determination Of Total Volatile Basic Nitrogen (Tvb-n)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have highlighted their benefits in aquaculture, notably in enhancing growth performance, disease control, immune response improvement, and digestive enzyme activity [16,17]. Among these, Bacillus species are widely employed as probiotics in aquatic animals [18][19][20][21]. Studies have demonstrated that probiotics do not lead to drug resistance in aquatic species, making them viable antibiotic substitutes [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis , a well-studied exogenous probiotic in aquaculture, can colonize, grow and reproduce in the intestinal tract of aquatic animals, secreting and producing a variety of digestive enzymes and nutritional metabolites ( Liu et al., 2015 ; Shiu et al., 2015 ; Alan et al., 2016 ; Xu et al., 2016 ; Zuenko et al., 2017 ; Zhang et al, 2021a ). Moreover, its supplementation in diets has a strong beneficial effect on many kinds of fish, and no obvious toxicity has been found with an appropriate amount of supplementation ( Shiu et al., 2015 ; Xu et al., 2016 ; Liu et al., 2018 ; Adelina et al., 2019 ; Ahmadifard et al., 2019 ; Olmos et al., 2020 ; Wang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%